Period and Velocity as Statistical Concepts - Gordon, R. A. (Quarterly Journal of Economics, 1941)
Journal Article Period and Velocity as Statistical Concepts Get access K. A. Gordon K. A. Gordon University of California, Berkeley Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 55, Issue 2, February 1941, Pages 306–313, https://doi.org/10.2307/1882064 Published: 01 February 1941